Social media usage and cyberbullying: the moderating role of tie strength - Ni, Jinru; Fu, Hongyu; Zhu, Yajing; Li, Zewen; Wang, Shuyi; Su, Haoran (Frontiers in Psychology, 2025)
IntroductionCyberbullying is a pervasive issue in the digital age, closely linked to social media usage. However, existing research has largely overlooked the role of tie strength on social media platforms in shaping cyberbullying dynamics. This study, grounded in tie strength theory and medium theory, investigates the association between social media usage and cyberbullying, focusing on how tie strength moderates this relationship.MethodsA sample of 813 healthy adults (Mage = 20.06 ± 2.30 years, 498 females) completed an online survey, including the Chinese version of the Social Network Site Intensity Scale and the Cyberbullying Inventory for College Students (CICS).Results(1) Tie strength varies from platform to platform. The order of tie strength between users and the four platforms is as follows: WeChat > Bilibili > Weibo > Douyin. (2) Strong-tie social media platforms exhibited higher levels of users’social media engagement compared to those with weak ties. (3) Weak ties significantly moderated the relationship between social media usage and cyberbullying, whereas strong ties did not. Increased social media usage was associated with a higher likelihood of both engaging in and being a victim of cyberbullying on weak-tie platforms, while strong-tie platforms showed a lower likelihood of both engaging in or being a victim of cyberbullying with increased usage.ConclusionThese findings highlight the interplay between tie strength theory and medium theory in explaining cyberbullying dynamics and underscore the need for platform-specific interventions to address this pervasive issue.